Synthesis of Biodiesel from Feun Kase (Thevetia peruviana) Seed Oil Using NaOH Catalyst - Jefry Presson; Yohana Ivana Kedang; Maria Lilita Guterres; Risna Erni Yati Adu; Elisabeth Korbafo; Heri Suseno (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
The demand for biodiesel in the renewable energy sector continues to grow yearly. However, the majority of biodiesel sources currently still compete with the food sector. Feun Kase seeds contain high oil and do not compete with food, so they have prospects as a new source of biodiesel. This study aimed to find the optimal conditions for synthesizing biodiesel from Feun Kase seed oil, carried out through transesterification with four reaction variables: catalyst variation, time, temperature, and the molar ratio of oil/methanol. This study was equipped with parameter test data according to SNI (Indonesian National Standard) 7182:2015, also equipped with characterization using FTIR (Fourier Transform Infrared) and GCMS (Gas Chromatography Mass Spectroscopy). The highest biodiesel yield of 84.09% was obtained using optimum conditions of 1% NaOH catalyst, oil/methanol molar ratio of 1:6 at 70°C for 90 minutes of reaction. The test results of biodiesel parameters are density (851 kg/m3), smoke point (6°C), kinematic viscosity (5.35 cSt); acid number (1.08 mg KOH/gr), saponification number (159.32 mg KOH/gr), iodine number (78.62 g I2/100 g sample), flash point (165°C), and cetane number (62.86). FTIR analysis proved the presence of methyl esters with typical absorption at 1743 cm-1, 1195.87 cm-1, and 1436.97 cm-1. GCMS characterization showed that Feun Kase biodiesel was dominated by methyl oleate (53.45%), methyl palmitate (27.05%), methyl stearate (10.96%), and methyl linoleate (6.29%).